Development of guided inquiry-based student worksheets on the Pythagorean theorem to facilitate eighth-grade students' mathematical conceptual understanding - Novitasari, Novitasari; Heleni, Susda; Suanto, Elfis (Jurnal Gantang, 2026)
Students' mathematical conceptual understanding of the Pythagorean theorem remains limited because learning often does not actively engage them in constructing mathematical concepts. Consequently, many students experience difficulties understanding conceptual relationships, explaining solutions, translating contextual problems into mathematical models, and selecting appropriate procedures for solving problems. Student worksheets (LKPD) specifically designed for the Pythagorean theorem and systematically aligned with indicators of mathematical conceptual understanding are still limited. This study aimed to develop a valid and practical guided inquiry-based LKPD on the Pythagorean theorem. The study employed the 4-D development model, consisting of the define, design, develop, and disseminate stages. The developed LKPD integrates the five syntaxes of the guided inquiry model with indicators of mathematical conceptual understanding, including restating concepts, representing concepts in various mathematical representations, selecting appropriate procedures, and applying concepts to solve mathematical problems. Validation results showed an average score of 86.73%, indicating that the LKPD was valid. Furthermore, the practicality test involving 36 eighth-grade students of Class VIII.2 at SMP Negeri 8 Pekanbaru produced a score of 91.88%, indicating that the LKPD was very practical. Therefore, the LKPD meets the criteria for validity and practicality and can serve as an alternative instructional material for learning the Pythagorean theorem.